Tendencies to explicitation in 'A Legião Estrangeira' translated into English with the tittle The Foreign Legion by Giovanni Pontiero - Rocha, Celso Fernando [UNESP]; De Camargo, Diva Cardoso [UNESP] (Universidade Estadual de Maringa, 2012)
Some aspects involving explicitness within the literary translation process from Portuguese into English are analyzed. Clarice Lispector's 'A Legião Estrangeira' and its translation by Giovanni Ponteiro as The Foreign Legion, have been selected for current investigation employing the theoretical and methodological approach based on Baker's Corpus-based Translation Studies (1993, 1995, 1996, 2000) and Berber Sardinha's Corpus Linguistics (2004). The interrelations between the original and the translated texts and Ponteiro's solutions in his translation of preferential and recurring terms and idiomatic expressions are underscored and discussed.
Keywords: Clarice Lispector; Corpus Linguistics; Corpus-based Translation Studies; Giovanni Pontiero; Literary translation